Depression, Anxiety And Stress Among Medical And Allied Health Sciences Students At Sargodha Medical College - Muhammad Saeed Raza; Ahsan Maqbool; Sana Zahid; Shoaib Ahmad Malik; Ayesha Yousaf; Kashif Rauf (Journal of Rawalpindi Medical College)
Objective: This study attempts to determine the frequency of depression, anxiety and stress and associated factors among medical and allied health sciences students of Sargodha Medical College.